Influence of the Hydrophobicity of Pluronic Micelles Encapsulating Curcumin on the Membrane Permeability and Enhancement of Photoinduced Antibacterial Activity - Maria Antonia Tănase; Andreia Cristina Soare; Lia Mara Diţu; Cristina Lavinia Nistor; Catalin Ionut Mihaescu; Ioana Catalina Gifu; Cristian Petcu; Ludmila Otilia Cinteza (MDPI AG, 2022)
Apart from its well-known activity as an antimicrobial agent, Curcumin (CURC) has recently started to arouse interest as a photosensitizer in the photodynamic therapy of bacterial infections. The aim of the present study was to evidence the influence of the encapsulation of Curcumin into polymeric micelles on the efficiency of photoinduced microbial inhibition. The influence of the hydrophobicity of the selected Pluronics (P84, P123, and F127) on the encapsulation, stability, and antimicrobial efficiency of CURC-loaded micelles was investigated. In addition, the size, morphology, and drug-loading capacity of the micellar drug delivery systems have been characterized. The influence of the presence of micellar aggregates and unassociated molecules of various Pluronics on the membrane permeability was investigated on both normal and resistant microbial strains of E. coli, S. aureus, and C. albicans. The antimicrobial efficiency on the common pathogens was assessed for CURC-loaded polymeric micelles in dark conditions and activated by blue laser light (470 nm). Significant results in the reduction of the microorganism's growth were found in cultures of C. albicans, even at very low concentrations of surfactants and Curcumin. Unlike the membrane permeabilization effect of the monomeric solution of Pluronics, reported in the case of tumoral cells, a limited permeabilization effect was found on the studied microorganisms. Encapsulation of the Curcumin in Pluronic P84 and P123 at very low, nontoxic concentrations for photosensitizer and drug-carrier, produced CURC-loaded micelles that prove to be effective in the light-activated inhibition of resistant species of Gram-positive bacteria and fungi.